2022
DOI: 10.1159/000525891
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Antimicrobial Resistance: Surveillance among Visitors of a Tertiary Care Center, Riyadh, Saudi Arabia

Abstract: <b><i>Introduction:</i></b> Antimicrobial resistance (AMR) is a worldwide issue that was declared by the World Health Organization as a high-priority issue. However, there is a lack of awareness about AMR noticed in our community. Therefore, this study aims to assess the knowledge of the community regarding AMR. <b><i>Methodology:</i></b> A validated 24-item questionnaire was administered to the visitors of the outpatient clinic pharmacy waiting area to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Such a community still has some misconceptions and insufficient knowledge regarding AR [177]. Similar results were reported in the south-western region [174], Jazan, SA [178], university medical Saudi students [179], a tertiary care center, Riyadh, SA [180], Al Wazarat Health Center in Riyadh [181], while Jeddah population have more proper knowledge and awareness about AR [182,183]. The emergence and spread of AR are causes for great concern because of inadequate awareness of the risks associated with independent medication and antibiotic overuse.…”
Section: Discussionsupporting
confidence: 69%
“…Such a community still has some misconceptions and insufficient knowledge regarding AR [177]. Similar results were reported in the south-western region [174], Jazan, SA [178], university medical Saudi students [179], a tertiary care center, Riyadh, SA [180], Al Wazarat Health Center in Riyadh [181], while Jeddah population have more proper knowledge and awareness about AR [182,183]. The emergence and spread of AR are causes for great concern because of inadequate awareness of the risks associated with independent medication and antibiotic overuse.…”
Section: Discussionsupporting
confidence: 69%
“…One study by Alqarni et al [21] found younger age (31–40 years) having undergraduate or postgraduate education and being employed were significantly associated with better awareness and knowledge of AMR. The other study by Alduahimi et al [16] found similar results with factors such as the female gender and a health science background.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies from the Arab World have shown that the public often use social media (or the internet) as one of their sources of information about AMR and appropriate use of antibiotics [15]. In a recent study from Saudi Arabia, 28% of the participants (n = 111 of 397) reported such behavior, whereas about 9% (n = 17 of 193) of the participants in another recent study from Iraq reported it [7,16]. The larger percentage in the former study could be potentially justified by the fact that many of the included videos in this study were produced from Saudi Arabia (n = 22; 22.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study, along with other findings, highlights that adults generally possess a better understanding of AMR and CC compared to young adults [27,65,66]. This could be attributed to the fact that adults' increased vulnerability to both infectious and chronic diseases might contribute to their AMR knowledge, as it could lead to greater exposure to health information from healthcare professionals, thus enhancing their understanding [15,67]. This finding suggests a potential correlation between age and knowledge proficiency, potentially attributable to accrued life experiences, prolonged exposure to informational resources, as well as increased societal recognition and leadership roles within communities, facilitating easier access to information dissemination channels of both AMR and CC, whether through governmental initiatives or specialized training programs [68].…”
Section: Discussionsupporting
confidence: 62%